Case of osteopetrosis with multiple impacted primary and permanent teeth diagnosed at eight years old. Issue 1 (April 2023) - Okawa, Rena; Kadota, Tamami; Nagayama, Kayoko; Suehiro, Yuto; Masuda, Katsuhiko; Nakano, Kazuhiko
Abstract: Background: Osteopetrosis is a rare skeletal disease characterized by increased bone density caused by a malfunction of osteoclasts. Case presentation: An 8-year-4-month-old girl with multiple primary and permanent tooth impaction was diagnosed with osteopetrosis. In spite of typical manifestations of osteopetrosis in early childhood, including visual and hearing impairments, short stature, and dental abnormalities, diagnosis was severely delayed. Conclusion: Multiple impacted teeth may indicate a possible diagnosis of osteopetrosis. Dentists should perform an orthopantomography examination when eruption disturbances are encountered and systemic disease should also be suspected, with referral to a pediatrician when necessary.